Neural-Augmented Kelvinlet for Real-Time Soft Tissue Deformation Modeling - Shahbazi, Ashkan; Pereira, Kyvia; Heiselman, Jon S.; Akbari, Elaheh; Benson, Annie C.; Seifi, Sepehr; Liu, Xinyuan; Johnston, Garrison Lawrence Horswill; Ying Wu, Jie; Simaan, Nabil; et al. (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Accurate and efficient modeling of soft-tissue interactions is fundamental for advancing surgical simulation, surgical robotics, and model-based surgical automation. To achieve real-time latency, classical Finite Element Method (FEM) solvers are often replaced with neural approximations; however, naively training such models in a fully data-driven manner without incorporating physical priors frequently leads to poor generalization and physically implausible predictions. We present a novel physics-informed neural simulation framework that enables real-time prediction of soft-tissue deformations under complex single- and multi-grasper interactions. Our approach integrates Kelvinlet-based analytical priors with large-scale FEM data, capturing both linear and nonlinear tissue responses. This hybrid design improves predictive accuracy and physical plausibility across diverse neural architectures while maintaining the low-latency performance required for interactive applications. We validate our method on challenging surgical manipulation tasks involving standard laparoscopic grasping tools, demonstrating substantial improvements in deformation fidelity and temporal stability over existing baselines. These results establish Kelvinlet-augmented learning as a principled and computationally efficient paradigm for real-time, physics-aware soft-tissue simulation in surgical AI.